Extracellular Vesicles From the Dermatophyte Trichophyton interdigitale Modulate Macrophage and Keratinocyte Functions - Bitencourt, Tamires Aparecida; Rezende, Caroline Patini; Quaresemin, Natália Renault; Moreno, Pedro; Hatanaka, Otavio; Rossi, Antonio; Martinez-Rossi, Nilce Maria; Almeida, Fausto (Frontiers in Immunology, 2018)
The release of biomolecules critically affects all pathogens and their establishment of diseases. For the export of several biomolecules in diverse species, the use of extracellular vesicles (EVs) is considered to represent an alternative transport mechanism, but no study to date has investigated EVs from dermatophytes. Here, we describe biologically active EVs from the dermatophyte Trichophyton interdigitale, a causative agent of mycoses worldwide. EV preparations from T. interdigitale were examined using nanoparticle-tracking analysis, which revealed vesicular structures 20–380 nm in diameter. These vesicles induced the production of proinflammatory mediators by bone marrow-derived macrophages (BMDMs) and keratinocytes in a dose-dependent manner, and an addition of the EVs to BMDMs also stimulated the transcription of the M1-polarization marker iNOS (inducible nitric oxide synthase) and diminished the expression of the M2 markers arginase-1 and Ym-1. The observed M1 macrophages’ polarization triggered by EVs was abolished in cells obtained from knockout Toll-like receptor-2 mice. Also, the EVs-induced productions of pro-inflammatory mediators were blocked too. Furthermore, the EVs from T. interdigitale enhanced the fungicidal activity of BMDMs. These results suggest that EVs from T. interdigitale can modulate the innate immune response of the host and influence the interaction between T. interdigitale and host immune cells. Our findings thus open new areas of investigation into the host-parasite relationship in dermatophytosis.